Anterior bilateral temporomandibular joint dislocation: an emergency presentation - A. O. Taiwo; O. M. Gbotolorun; B. O. Ile-Ogedengbe (Nigerian Dental Association, 2010)
Anterior dislocation of the temporomandibular joint (TMJ) though an infrequent presentation at the emergency department; often demands an immediate reduction to relieve discomfort and prevent adverse long-term sequelae. A simple and effective technique to reduce the dislocation is successfully demonstrated by putting the operator's thumbs over the molar teeth of the patient and pushing the dislocated jaw downward and backward. We report the case of a patient who presented at our accident and emergency department with bilateral anterior TMJ dislocation and was successfully reduced with this simple technique.